An Easy and Efficient Strategy for the Enhancement of Epothilone Production Mediated by TALE-TF and CRISPR/dcas9 Systems in Sorangium cellulosum - Ye, Wei; Liu, Taomei; Zhu, Muzi; Zhang, Weimin; Huang, Zilei; Li, Saini; Li, Haohua; Kong, Yali; Chen, Yuchan (Frontiers in Bioengineering and Biotechnology, 2019)
Epothilones are a kind of macrolides with strong cytotoxicity towards cancer cells and relatively lower side effects compared with taxol. Epothilone B derivate ixabepilone has been used for the clinical treatment of advanced breast cancer. However, the low yield of epothilones and the difficulty in the genetic manipulation of S. cellulosum limited their wider application. Transcription activator-like effectors-Trancriptional factor (TALE-TF)-VP64 and clustered regularly interspaced short palindromic repeats (CRISPR)/dCas9-VP64 have been demonstrated as effective systems for the transcriptional improvement. In this study, promoter for the epthilone biosynthesis cluster was obtained and the function has been verified. The TALE-TF-VP64 and CRISPR/dcas9-VP64 target P3 promoter were electroporated into Sorangium cellulsoum strain So ce M4, the transcritional levels of epothilone biosynthesis related genes were significantly up-regulated. The yield of epothilone B was improved by 2.89 fold and 1.53 fold by the introduction of recombinant TALE-TF-VP64-P3 and dCas9-VP64-P3 elements into So ce M4. The epothilone D yield was also improved by 1.12 fold and 2.18 fold in recombinant dCas9-So ce M4 and TALE-VP64 strains, respectively. And the transcriptional regulation mechanism of TALE-TF-VP64 and the competition mechanism with endogenous transcriptional factor were investigated by electrophoretic mobility shift assay (EMSA) and Chromatin Immunoprecipitation (ChIP), demonstrating the combination of P3 promoter and TALE-TF element and the competition between TALE-TF and endogenous transcritional protein. This is the first report on the transptional regulation of epothilone biosynthetic gene cluster in S. cellulosum using TALE-TF and dCas9-VP64 system, and the regulatory mechanism of TALE-TF system for epothilone biosynthesis in S. cellulosum was also firstly revealed, thus shedding light on the metabolic engineering of S. cellulosum to improve epothilones yields substantially and promoting the application of epothilones in biomedical industry.